Borderlanders: academic staff being and becoming doctoral students. Issue 3 (3rd April 2021) - Billot, Jennie; King, Virginia; Smith, Jan; Clouder, Lynn
ABSTRACT: The notion of borderlands implies a boundary demarcating a crossing to/from an unfamiliar territory. It is a productive metaphor for dual-status academics – those employed in academic roles in universities who concurrently undertake doctoral studies. We argue that dual-status academics dwell in an extended form of boundary crossing, potentially to-ing and fro-ing several times a day, inducing unforeseen impacts on identities. Having previously reported the structures that frame this boundary crossing, here we re-analyse an existing data set for the visceral: the stories of code-switching, of peripheral existence and of agentic purpose. Our data indicate that dual-status academics adopt a transactional approach to doctoral supervision that results in a 'fight or flight' response to the emotional and relationship challenges these borderlands present, with implications for how academics manage colleague supervision, both as supervisor and supervisee. Our study leads us to recommend tailored institutional and supervisory support pedagogies for these academics.